A study of patients poisoned with household products in emergency department of a tertiary care hospital in eastern Nepal - Mandal, Madan Krishna; Mandal, Namita Kumari (Journal of General Practice and Emergency Medicine of Nepal, 2025)
Introduction: Poisoning due to household substances is frequently observed, especially in low- and middle-income nations such as Nepal. Nevertheless, there is a scarcity of information regarding their clinical characteristics, treatment approaches, and patient outcomes. Method: A descriptive cross-sectional study was conducted in the Emergency Department of Nobel Medical College Teaching Hospital, Eastern Nepal. All adult patients presenting with confirmed or suspected household product poisoning during the study period were included. Data on demographics, poisoning agents, clinical features, management, and outcomes were collected using a structured proforma. Result: Among 70 cases analyzed, 47(67.14%) were female, with the 15-30 years age group most affected. Corrosive agents such as phenyl, acid, and kerosene were the most frequently implicated. Intentional ingestion accounted for 59(84.28%) of cases, largely with suicidal intent. Common symptoms included nausea, vomiting, oral burns, and respiratory distress. Gastric lavage and supportive care were primary treatments. Most patients recovered with timely intervention; however, 5(7.14%) developed complications, and the case fatality rate was 3(4.28%). Conclusion: Household product poisoning is a significant public health issue in Eastern Nepal, especially among young females. Corrosive agents are the leading cause. Early diagnosis and prompt treatment are vital. Public awareness and stricter regulation of toxic household chemicals are strongly recommended.